1997
DOI: 10.1021/ja963197x
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophile-Assisted Cleavage of Benzyltrialkylsilane Cation Radicals

Abstract: The cation radicals of benzyltrialkylsilanes have been generated using photoinduced electron transfer and characterized using transient absorption spectroscopy. Absolute rate constants for nucleophile-assisted C-Si bond cleavage have been determined, for different nucleophiles in different solvents and with different substituents on the phenyl ring. The short lifetime (<10 -9 s) of the parent benzyltrimethylsilane cation radical in acetonitrile was unambiguously shown to be due to a rapid nucleophile-assisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
117
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(124 citation statements)
references
References 61 publications
7
117
0
Order By: Relevance
“…The best result was obtained by the addition of 1 equiv of L-lactic acid based on 1 to give 4 in 72% de 1 In the presence of MeOH or H 2 O instead of AcOH as a proton source, the reaction proceeded slowly to give a complex mixture. 2 The hydrogenation of compound 1 by Pd/C has been reported to proceed in a syn selective manner [19]. We prepared syn-rich mixtures of 3 and 4 by the hydrogenation of 1 by Pd/C and allylation of the syn-rich mixture of 4 by NaH and allyl bromide.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The best result was obtained by the addition of 1 equiv of L-lactic acid based on 1 to give 4 in 72% de 1 In the presence of MeOH or H 2 O instead of AcOH as a proton source, the reaction proceeded slowly to give a complex mixture. 2 The hydrogenation of compound 1 by Pd/C has been reported to proceed in a syn selective manner [19]. We prepared syn-rich mixtures of 3 and 4 by the hydrogenation of 1 by Pd/C and allylation of the syn-rich mixture of 4 by NaH and allyl bromide.…”
Section: Resultsmentioning
confidence: 99%
“…The primary step is the generation of radical cation of Phen (Phen ?• ) and the radical anion of 1 (1 -• ) through a one-electron transfer from the excited singlet state of Phen ( 1 Phen*) to 1. The secondary electron transfer from 2 to Phen ?• produces the radical cation of 2 (2 ?• ), which gives the allyl radical via the nucleophile-assisted cleavage of the C-Si bond [18][19][20]. In the presence of a proton source, the protonation at the b-position to the cyano groups of 1 -• predominantly takes place to generate the radical 5.…”
Section: Resultsmentioning
confidence: 99%
“…The (CH 3 ) 3 -Si ? cation is known to absorb in the same spectral region (k max = 530 nm) [20]. This cation was not present in the pulse radiolysis experiments.…”
Section: Stable Product Analysismentioning
confidence: 97%
“…In principle, the kinetics of this reaction could be improved by utilizing a cationic oxidant and an aromatic cooxidant in accord with Dinnocenzo's studies. 12 When 15 was irradiated in the presence of NMQPF 6 and the cooxidant tert-butylbenzene, shown by Kochi 16 to form a radical cation that stable toward fragmentation, the reaction proceeded to form 16 within 20 min. As illustrated in Scheme 3.10, other examples in the same report demonstrated that five-, seven-, and eight-membered rings could also be formed in good yields.…”
Section: Electron Transfer-initiated Cyclization Reactionsmentioning
confidence: 99%